PERAN BUDAYA ORGANISASI MEMODERASI PENGARUH KOMPETENSI DAN STRES KERJA TERHADAP KINERJA GURU (Studi Kasus Pada SMK Negeri Sub Rayon SMK 01 Kota Semarang) - 11.52.02.0158, Sunar (Jurnal Mahasiswa Pasca Sarjana, 2013)
The purpose of this study is to examine and analyze the effect of competence, Job Stress and organization culture on teacher performance, as well as the moderating role of organization culture in relation competencies and job stress on teacher performance.The population in this study is teachers at Vocational high school state (SMK) in sub rayon 01 SMK Kota Semarang, amounting to 248 people. Samples were analyzed is 131 respondents. Nonprobability sampling technique using for make sampling with convinience sampling techniques. Methods of data collection were performed using a questionnaire with a scale linkert in the range 1-7. The data is processed and analyzed primary data derived from responses to questionnaires by respondents. Testing the validity and reliability of the instrument through. Analysis of the data using linear regression.The results showed that competence does not affect the performance of teachers. Job stress is a significant negative effect on teacher performance. Organization culture does not affect the performanceâs teacher. Organizational culture did not moderate the relationship with teacher performance competency, but moderate relationship with job stress weaken the role of teacher performance relationship. Keywords: Competence, Job stress, organizational culture and Teacher Performance